Prognostic bioindicators in severe COVID-19 patients. (May 2021) - Bergantini, L.; Bargagli, E.; d'Alessandro, M.; Refini, R.M.; Cameli, P.; Galasso, L.; Scapellato, C.; Montagnani, F.; Scolletta, S.; Franchi, F.; Valente, S.; Bennett, D.; et al.
Abstract: Background: Severe acute respiratory syndrome caused by novel coronavirus 2 (SARS-CoV-2) emerged in Wuhan (China) in December 2019. Here we evaluated a panel of biomarkers to phenotype patients and to define the role of immuno-inflammatory mediators as biomarkers of severity. Materials and methods: Serum samples were obtained from 24 COVID-19 patients on admission to hospital, before any treatment or infusion of intravenous steroids or invasive ventilation. KL-6 IL-6 and C-peptide were measured by chemiluminescent enzyme immunoassay. IL-6 assay was validated for accuracy and precision. The validity of variables used to distinguish severe from mild-to-moderate patients was assessed by areas under curves (AUC) of the receiver operating characteristic (ROC) and logistic regression was performed to combine parameters of the two groups. Results: In the severe group, IL-6, CRP and KL-6 concentrations were significantly higher than in mild-to-moderate patients. KL-6, IL-6 and CRP concentrations were directly correlated with each other. ROC curve analysis of the logistic regression model including IL-6, KL-6 and CRP showed the best performance with an AUC of 0.95. Conclusions: Besides corroborating previous reports of over-expression of IL-6 in severe COVID-19 patients requiring mechanical ventilation, analytical determination of other mediators showed that IL-6 concentrations were correlated with those of KL-6 and CRP. The combination of these three prognostic bioindicators made it possible to distinguish severe COVID-19 patients with poor prognosis from mild-to-moderate patients.